MEDIA FILTRASI UNTUK PENURUNAN KANDUNGAN (Fe, Mn) SERTA pH DI PT. ALLIED INDO COAL JAYA PARAMBAHAN, SAWAHLUNTO, SUMATERA BARAT - Refky Adi Nata; Tila Restiawati (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. Acid Mine Drainage is a serious problem for the environment. In addition because of the low pH, acid mine drainage also contains metal ions such as Fe and Mn. In PT Indo Allied Coal Jaya Sawahlunto, West Sumatra there was standing water on the mining front, if not clear treatment for acid mine water, quality of water the content of the metal. The purpose of this research is to know the levels of metals and pH with the help of media filtration using five ingredients i.e. activated carbon, coir, evergreen leaves, rice husk and river sand. The parameters examined were pH, iron (Fe) and manganese (Mn). The results obtained showed that all pH levels as well as Fe and Mn rising and only 1 sample 4 sample i.e. decline on testing Fe. From the results of the highest pH are present in sample 2 of 8, whereas the lowest was at sample 1 of 7.48. For the content of Fe, the value highest content found in sample 2 of 0.37 mg/l and the lowest is present on the samples 3 and 4 with 0.02 mg/l. While for Mn the highest found in sample 2 i.e. registration 0.91 mg/l and Mn for the lowest contained on the sampe 4 i.e. amounted to 0.39 mg/l. Keywords: filtrasi, acid mine drainage, sabut kelapa, daun cemara, activated carbon